2011
DOI: 10.1159/000333207
|View full text |Cite
|
Sign up to set email alerts
|

Tailor-Made Therapy for Viral Hepatitis: Recent Advances

Abstract: Combination therapy of pegylated interferon-α with ribavirin (PEG-IFN/RBV) is a standard of care for chronic hepatitis C (CHC). The majority of CHC patients are infected with HCV genotype I. The recent discovery revealed by a genome-wide association study technology provides the important role of interleukin-28B (IL28B) and inosine triphosphatase (ITPA) in HCV infection. In addition, response to PEG-IFN/RBV therapy is correlated with insulin resistance, hepatic steatosis, and hepatic fibrosis in CHC patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…More recently, several genome-wide association studies have identified genetic variations within the intergenic region of interleukin 28B (IL28B), which is associated both with spontaneous HCV clearance [20] and SVR to antiviral therapy in HCV-G1-infected individuals [21,22,23,24]. Moreover, total PEG-IFN-α dose has been associated with treatment outcome in multivariate analysis [25].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several genome-wide association studies have identified genetic variations within the intergenic region of interleukin 28B (IL28B), which is associated both with spontaneous HCV clearance [20] and SVR to antiviral therapy in HCV-G1-infected individuals [21,22,23,24]. Moreover, total PEG-IFN-α dose has been associated with treatment outcome in multivariate analysis [25].…”
Section: Introductionmentioning
confidence: 99%